Internet collaborative projects as an effective educational method in teaching writing - SAMOYLENKO, Nataliya (Journal of Education, Technology and Computer Science, 2013)
In the article the Internet collaborative projects and information communicationtechnologies as one of the pedagogical technologies in teaching students’writing skills is considered. An author exposes one of aspects of preparation offuture specialists for international communication, related to integration of traditionaland innovative methods of teaching.The basic tasks of using the project work are analysed: teacher’s training tothe professional using the project work on the basis of information communication technologies; forming for the teachers the abilities of using the project workin their professional activity; improving the educational process at the secondaryand higher school on the basis of the project work; development of methods ofusing the project work in teaching foreign languages and developing writingskills.